BMV-CSC Patch: Sel Punca Jantung dengan Biomimetic Microvessel berbasis HUVEC sebagai Inovasi Potensial untuk Terapi Infark Miokardium Akut - Yitzchak Millenard Sigilipu (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Coronary Heart Disease (CHD) is the main global cause of morbidity and mortality. The most common form of CHD is myocardial infarction which contributes to more than 15% of death. Cardiac stem cell-based therapy (CSC) is a promising approach to treat the condition. The main issue hindering efficacy and further development of the approach is the low retention and viability of stem cells after intra myocardial injection on ischemic heart. In order to address the issue, a novel strategy to create a vascularized cardiac patch using the microfluid with hydrodynamic focusing technique. The cardiac patch will be integrated Biomimetic Micro Vessels (BMV) alongside human umbilical vein endothelial cells (HUVEC) on the luminal surface. A study reported that the endothelium of BMV mimics the architecture and natural functioning of the capillaries. Vascularized cardiac patch (BMV-CSC) will release paracrine factors higher than original co-cultured human CSC and HUVEC after seven days of in vitro culture. In acute myocardial infract (AMI) rat model, the BMV-CSC patch induced mitotic activities of cardiomyocytes in peri-infarcted area after 4 weeks of implantation. Significant increase in the density of myocardial capillaries in infarct area compared to the conventional cardiac patch was also reported. The significant benefits of BMV-CSC patch showed that this approach is a potential method for AMI therapy.